UPAYA GURU PENDIDIKAN AGAMA KATOLIK DALAM MENGEMBANGKAN KEMAMPUAN AFEKTIF SISWA MENURUT PERSPEKTIF TAKSONOMI BLOOM - Simbolon, Erikson; Simanjuntak, M. Marihot; Hutahaean, Dina Novita Paskah (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2023)
The purpose of this study was to determine the efforts of Catholic Religious Education teachers in developing the affective abilities of students at RK Deli Murni Bandar Baru Junior High School. The informants in this study were PAK teachers, school principals, peer teachers and students. The method used in this study is a qualitative method with observation techniques, interviews and documentation. The findings of this study are the teacher presenting interesting material, looking neat while teaching, motivating students while teaching, building students' self-confidence by involving students taking turns leading prayers and singing when studying Catholicism. Students focus their attention on the teacher when explaining learning material.